New Approaches to Assess Fertility in Domestic Animals: Relationship between Arterial Blood Flow to the Testicles and Seminal Quality - Ana Velasco; Salvador Ruiz (Animals, 2020)
The early identification of infertile males improves reproduction efficiency at a production level and is essential to secure high production rates. Before entering a breeding program, males must pass an initial breeding soundness examination (BSE) which consist of several diagnostic exams whose end point is to estimate their future fertility. There is ongoing research to find new markers that allow better identification of fertile males. Doppler mode allows the quantitative and qualitative evaluation of the irrigation of organs. When evaluating the reproductive system, Doppler mode has been successfully used for the evaluation of the uterine and ovarian irrigation. In males, it is gaining relevance for the evaluation of testicular irrigation. Researchers have found a relationship between pulsed-wave Doppler velocimetric parameters and seminal quality in various domestic animal species. This suggests Doppler ultrasound parameters should be considered as objective parameters to evaluate testicular function. In this review, we analyze the results in the main domestic animal species and discuss the differences and similarities among the results. We also discuss the effect of the location of the measurements, breed, season and laterality in the measurement of Doppler velocimetric parameters as well as the impact and limitations of this method of assessing breeding soundness.